(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The level of self-assessment of a healthy lifestyle and health of graduates of secondary schools in the city of Kryvyi Rih was studied. There is a low level of self-control among young people over their health, ignoring the principles of a healthy lifestyle. According to the results of observations, students, although they have mastered some knowledge about the problems of a healthy lifestyle, do not apply them in their personal lives. Teachers and parents of students are invited to help them master new thinking about the need to be responsible for their health, and a healthy lifestyle.